2012
DOI: 10.3832/efor0697-009
|View full text |Cite
|
Sign up to set email alerts
|

Bird diversity in Turkey oak (Quercus cerris) coppices and transitory stands in the northern Apennines

Abstract: IntroduzioneIl ceduo è un elemento importante del paesaggio forestale italiano: è governata a ceduo più della metà dei boschi italiani e in alcune regioni, soprattutto dell'Italia centrale, la percentuale di boschi cedui sul totale della superficie forestale è molto più elevata (oltre l'85% in Toscana -Hofmann et al. 1998). I cambiamenti che hanno interessato il paesaggio dell'intero territorio nazionale (Falcucci et al. 2007) ed in particolare, nel breve e nel lungo periodo, i paesaggi montani (Vos & Storte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In addition, Garadnai et al (2010) in their forest patch scale study, corroborated by other studies (Bartha et al 2008), have shown that actively managed beech coppices host a wider pool of vascular plants than abandoned coppices. This is consistent with the findings of Tellini Florenzano et al (2012) who showed that, although richness in forest bird species is positively related to stand age for both coppice and young growth, the forest specialists did not seem to be negatively influenced by the amount of open spaces.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Garadnai et al (2010) in their forest patch scale study, corroborated by other studies (Bartha et al 2008), have shown that actively managed beech coppices host a wider pool of vascular plants than abandoned coppices. This is consistent with the findings of Tellini Florenzano et al (2012) who showed that, although richness in forest bird species is positively related to stand age for both coppice and young growth, the forest specialists did not seem to be negatively influenced by the amount of open spaces.…”
Section: Discussionsupporting
confidence: 92%
“…In the Northern Apennines (including the study area), the presence of a significant proportion of conifers is a decisive factor for the occurrence of numerous bird species [65], including, among the target species, Lophophanes cristatus and the Dryocopus martius [71]. Mixed forests generally have heterogeneous stands, providing a greater range of nesting and foraging sites [72,73].…”
Section: Biodiversity Conservationmentioning
confidence: 99%
“…The dispersal performance of white oak and the response of seedlings, in terms of establishment and growth, in addition to changes in understorey diversity [22,30] and cover [25,[31][32][33][34] were studied; moreover, the potential distribution and composition of the ornithological community were also taken into account, as these are considered good indicators of biodiversity [35,36]. The main aim was to evaluate the possible recovery of old-growth forest patches over a long time scale and the effectiveness of regeneration of white oak, which is the basic prerequisite to maintain the local population and preserve its genetic variability.…”
Section: Introductionmentioning
confidence: 99%